2020
DOI: 10.13031/trans.13620
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present, and Future of Irrigation on the U.S. Great Plains

Abstract: Highlights Irrigation is key to the productivity of Great Plains agriculture but is threatened by water scarcity. The irrigated area grew to >9 million ha since 1870, mostly since 1950, but is likely to decline. Changes in climate, water availability, irrigated area, and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 153 publications
0
44
0
Order By: Relevance
“…The status of SDI at the beginning of the last decade within the entire U.S. was summarized by Lamm et al (2012a), who also reported the opportunities and challenges that exist for SDI adoption. The past, present, and future of irrigation in the Great Plains were discussed by Evett et al (2020b), who noted the growing interest and use of SDI and other advanced irrigation technologies and their importance in the future.…”
Section: Sdi In Comparison To Alternative Irrigation Systems Without a Specific Cropmentioning
confidence: 99%
“…The status of SDI at the beginning of the last decade within the entire U.S. was summarized by Lamm et al (2012a), who also reported the opportunities and challenges that exist for SDI adoption. The past, present, and future of irrigation in the Great Plains were discussed by Evett et al (2020b), who noted the growing interest and use of SDI and other advanced irrigation technologies and their importance in the future.…”
Section: Sdi In Comparison To Alternative Irrigation Systems Without a Specific Cropmentioning
confidence: 99%
“…Since precipitation gradients exist in the U.S. Great Plains from western to eastern regions (Evett et al, 2020), three subregions were classified for each state as western (100 o W towards west), central (between 97 o and 100 o W), and eastern ( 97 o W towards east). Figure 8 displays the time series of EM02 modeled, iEM02 modeled, and observed soil temperatures only covering winter wheat growing seasons (October 1 to June 30) for four growing seasons from 2015 to 2019 (validation periods) in Nebraska and Kansas.…”
Section: Spatial and Temporal Modeling Performancementioning
confidence: 99%
“…A reliable estimate of soil temperature (Ts) is useful to understand agricultural ecological systems, hydrological processes, and land-atmosphere interactions (Lembrechts et al, 2020;Qi et al, 2016;Zhang et al, 2018) due to the fact that Ts governs physical, chemical, and biological processes of the soil and interactions between the atmosphere and land-surface (Smith, 2000;Soong et al, 2020). In particular, Ts has been widely used for a better understanding of changes in soil moisture (Lakshmi et al, 2003), the ecosystem carbon balance (Goulden et al, 1998), and the nitrogen mineralization process (Persson and Wirén, 1995) although a larger prevalence of air temperature observations are available as a soil temperature proxy. From a practical perspective, Ts is critical for agricultural system models such as the crop environmental resource synthesis (CERES) models to assess the impacts of extreme climate on crop production and stress tolerance, thereby allowing producers to better prepare for proactive and reactive field management (Bergjord et al, 2008;Persson et al, 2017;Williams et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Corn, wheat, soybean and forages are cultivated over 55 million ha, producing 22% of the total crop value in the USA. About 8 million ha of this area is irrigated, the result of a rapid expansion which started in the 1950s with the invention of centre pivot irrigation systems, rural electrification, and improved well drilling and pump technologies (Evett et al, ). Initially, farmers thought that the Ogallala aquifer, the main water source, was unlimited; however, they soon found that, especially in the southern and western parts of the aquifer, their pumping exceeded the recharge so that the water table began to decline (Scanlon et al, ).…”
Section: What Does Energy Access Change?mentioning
confidence: 99%